Produktivitas dan Efisiensi Teknis Usaha Perkebunan Kopi di Sumatera Selatan dan Lampung - Zen, Fauziah; Budiasih, Budiasih (Jurnal Ekonomi dan Pembangunan Indonesia, 2018)
Coffee is the result of Indonesian plantations that have high competitiveness in the international market. However, coffee plantations in Indonesia have low productivity compared to other major coffee producing countries. This study aims to conduct a study of the productivity and technical efficiency of households coffee plantation business in the coffee producing center in Indonesia. The results of this study indicate that more than 50% of coffee plantation businesses in each of provinces have low productivity and medium technical efficiency. Education level is a variable that can increase productivity and technical efficiency significantly.